A proposed group guidance program for the Holy Cross College of Digos - Bana, Aquilino L. (Animo Repository, 1973)
v. 2. This study aims to determine the validity and usefulness of the students' College Entrance Test (CET) results to the Holy Cross College of Digos for the various purposes for which they have been intended, namely, for admission into college, for prediction of college success, for educational and vocational counseling, for students' curricular placement, and for selection of student assistants in various offices as a means of helping poor but capable students. The total number of samples used were 121 freshmen taken randomly from the various degree/non-degree programs of the college. The sample was drawn from students whose CET and GPA first semester were available and who were carrying an academic load of at least 15 units for the semester. The instruments used were the CET overall score (CET OVL), mental ability subtests (CET MA), CET subject proficiency subtests (CET SP), and CET English (CET ENG) as the criterion variables, and the college grade average (GPA) and college English (Col Eng) as the predicted variables. In order to make the relationship between the criterion and the predicted variables parallel with each other, a conversion table was devised. A total of 11 tables were presented which showed the means and standard deviations of the criterion and the predicted variables, correlation indices, the standard error of estimate, and the pass and fail expectancy table. Based on the findings of the study, it was concluded that the CET was valid for the prediction of the college freshmen students' first semester academic success and as such, was valid for admission purposes in the Holy Cross College of Digos. The CET English score predicted the students' college English performance during the first semester. The correlation pattern obtained in the association of CET OVL, CET MA, CET SP and college GPA held true for the various degree/non-degree programs. Therefore, the CET was a valid predictor of academic success of the course program. A CET T-score of 35 was found to be an appropriate cut-off score v. 3. The main problem in this case study is the unhealthy relationship between the client and the step-father. Initially, all materials relevant to the case were gathered. Sources of the data were interviews with the subject and the significant others, personality test (Minnesota Multiphasic Personality Inventory), and personal knowledge of the writer about the case. The manifested mal-adapted behavior of Pepito was a deliberate show of rebelliousness against the step-father due to the step-fathers intolerance and lack of understanding. On the other hand, the step-fathers behavior stemmed from the clients non-compliance of his regimented rule. The prejudices that one harbored against the other caused the breakdown of the channels of communication. The counseling techniques used in this particular case was influenced largely by Roger's non-directive counseling, Patterson's relationship therapy, and Ellis rational emotive therapy. The specific techniques were acceptance, empathy and understanding, silence, reflection of feelings, summary-clarification, suggestion, reassurance, reeducation and verbal reinforcement. The counseling sessions had brought about notable changes in the behavior of the client among which were: a) it had lessened his anxiety, b) the client had realized the evil of mandrax and had avoided it and c) it had developed in him optimistic view of life. The counseling approach was not a total success as the counselor-trainee failed to modify the behavior of the step-father, which was vital for the attainment of the objectives.